EDUKASI DAN DEMONSTRASI PEDOMAN GIZI SEIMBANG UNTUK ANAK SEHAT DAN BERPRESTASI - Miftahul Jannah; Indah Kusumaningrum (P3M Universitas Aisyiyah Surakarta, 2019)
School-age children tend to have poor eating behavior and lack of knowledge regarding nutrition, whereas that age group is the most vulnerable to malnutrition. This activity aimed to increase the knowledge about balanced nutrition guideline among students in State Elementary School Pulogebang 11, East Jakarta. This activity was conducted among all 4th grade students which numbered 109 students, in February 2019. The details of the activity are (1) education and demonstration about balanced nutrition guideline, in the form of lectures, games, singing, and exercise; (2) nutritional status assessment by measuring body weight and height of the students; and (3) food safety measurement by checking borax and formalin contained in snacks. The results of this activity shows an increase in knowledge related to balanced nutrition guideline, evidenced by students being able to answer and complete the game correctly. In terms of food safety, there are no snacks that contain formalin and borax. However, some snacks still contain other food additives, such as artificial sweetener, coloring, and flavoring.Â Food vendors also still lack of hygiene and sanitation. Based on nutritional status measurements, the prevalence of very thi, thin, normal, overweight, and obese were 4.6%, 7.3%, 59.6%, 12.8%, and 15.6% respectively.